2018
DOI: 10.1111/trf.14553
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in detection of antibodies against hepatitis E virus in US blood donor samples using commercial assays

Abstract: Although similar percentages of IgG anti-HEV/total anti-HEV detection were observed across the three commercial assays, each assay detected a unique sample subpopulation and was heteroskedastic when compared pairwise. Discordance was higher among anti-HEV IgM assays, but a recent HEV infection rate of at least 0.18% was estimated based on assay concordance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Third, although interrun repeatability was a requirement for incident‐ or reexposure categorization, we cannot exclude the possibility of false‐positive IgG anti‐HEV results because we did not independently verify reactivity (e.g., via western blot immunoassay) and our 31% frequency of IgG anti‐HEV reactivity is high. Noting that RADAR patient‐recipients were older (91% and 74% at least 50 and 60 years old, respectively) and predominantly male (54%), our IgG anti‐HEV frequency is consistent with several of those reported for older US subpopulations (see discussion below about prevalence).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Third, although interrun repeatability was a requirement for incident‐ or reexposure categorization, we cannot exclude the possibility of false‐positive IgG anti‐HEV results because we did not independently verify reactivity (e.g., via western blot immunoassay) and our 31% frequency of IgG anti‐HEV reactivity is high. Noting that RADAR patient‐recipients were older (91% and 74% at least 50 and 60 years old, respectively) and predominantly male (54%), our IgG anti‐HEV frequency is consistent with several of those reported for older US subpopulations (see discussion below about prevalence).…”
Section: Discussionsupporting
confidence: 86%
“…In a study of more recently collected (during 2015) ARC samples, which included approximately 1600 from donors 50 years old or older and testing with a Wantai IgG anti-HEV ELISA, reactive frequencies ranged from approximately 16% for 50-to 55-year-old donors to approximately 44% for those between 80 and 93 years old. 19 Incident infections are also likely to be frequent in older men 53 ; although the frequency of incident HEV exposures among RADAR patient-recipients was higher than that reported for general populations, 1,53 our data may reflect higher incidence in an older and predominantly male RADAR population. 20 During recent years, there has been increasing recognition of the risk of transmitting HEV by transfusion outside of the United States.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Vollmer and coworkers tracked 10 healthy blood donors with asymptomatic genotype 3 HEV infection and found that viraemia could last from less than 10-52 days while IgM was detected (Wantai) from 46 to 154 days following RNA detection [31]. Thus, while anti-HEV IgM may represent a marker of recent HEV infection, its detection (absent HEV RNA) could not be used as a reliable screening marker [32].…”
Section: Discussionmentioning
confidence: 99%